Examining the Needs of Families of School-Aged Children with an Autism Spectrum Disorder - Brown, Hilary (2010)
Thesis (Master, Community Health & Epidemiology) -- Queen's University, 2010-07-26 11:11:27.456 Background. Children with autism spectrum disorders have complex needs requiring a broad range of supports. High demand for autism services has led to gaps in the provision of care, and there is little research examining whether families of school-aged children receive services reflective of their needs. Objectives. The objectives of this thesis were to describe unmet needs reported by parents of school-aged children with an autism spectrum disorder and to examine the association between the child’s level of functional independence and the parent’s reported level of unmet need. Methods. A review of the literature on needs assessments in autism was performed. A cross-sectional study was then conducted among parents of 101 children who (1) had an autism spectrum disorder, (2) were between the ages of 6 and 13 years, and (3) were living in Manitoba, South Eastern Ontario, Prince Edward Island, or Newfoundland and Labrador. Data were collected using a written questionnaire (Family Needs Questionnaire, Impact on Family Scale, demographic questions) and a telephone interview (Scales of Independent Behaviour-Revised, service use questions). Log binomial regression was used to examine the association between the child’s functional independence and the parent’s perceived unmet needs. Results. The most commonly reported unmet needs were related to social inclusion for the child, information about special programs and services, and continuity of support. Families of children with high functional independence had lower unmet need compared to families of children with moderate functional independence (RR = 0.81, 95% CI = 0.67-0.99). Families of children with high functional independence, and who perceived a high level of impact of the child’s disability on the family, had greater unmet need (RR = 1.22, 95% CI = 1.03-1.45). Conclusion. This thesis identifies family needs which have not been met by the service system. ...